Surface pKa determination of benzoic acid modified gold electrodeby electrochemical and contact angle measurement methods - Ali Solak; Gamze Abacıoğlu; Zafer Üstündağ; Serkan Demirci; Aybüke Turan; Haslet Ekşi; Remziye Güzel; Sebahattin Balcı (MANAS: Journal of Engineering)
pKa values of the organic surfaces were determined with ionizable carboxylic acid groups, obtained by the modification of gold electrode by reduction of p-benzoic acid diazonium tetrafluoroborate and oxidation of p-aminobenzoic acid. Cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS) techniques were used in the surface pKa determination, by exploiting the barrier effect arising from the charged nature of the surface against the electrochemistry of Fe(CN)64-/3- redox probe. Contact angle measurement (CAM) technique was also used to compare the accuracy of the surface pKa values acquired by electrochemical methods. pKa values for Au-BA were found as 2.938±0.283, 4.128 ± 0.342 and 4.251±0.089 by CV, EIS, and CAM, respectively : while the values are 4.084±0.101 5.326±0.323 and 5.102±0.147 for Au-NHBA.